Из наблюдений над словообразованием в списках Литовского Cтатута 1529 г. - Власова, Т. П. (Kalbotyra, 1986)
The present paper deals with the formation of one-rooted nouns in four manuscripts of Lithuanian Statute of 1529 written in the Old Byelorussian language. Comparative analysis helped to reveal the differences of word-formation in the given sources.